Experiences and Challenges of Hijra (Transgender) People in Accessing Healthcare Services: A Qualitative Study in Rajshahi City Corporation - Md. Mahmud Hasan; S. M. Mokhlasur Rahman; Arafat, Md. Yeasir (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
In South Asia, Hijras are transgender, intersex, or eunuch people who live in close communities. In Bangladesh, they remain socially excluded and stigmatized. Although their gender identity is legally recognized, studies show they still face barriers in accessing healthcare. This research explores the healthcare experiences of Hijras in different service sectors. It is based on 79 in-depth interviews and 3 key-informant interviews, analyzed through thematic analysis. Findings show that public hospitals only provide male- and female-focused facilities, with no separate arrangements for Hijra patients. Many faced verbal harassment, blame for their illnesses, and unequal treatment. Health providers also lacked awareness of Hijra identity and culture. The study recommends formally including Hijra as a gender category in the healthcare system to reduce discrimination and ensure fair healthcare access for them.